PROGRAM EKONOMI PESANTREN DALAM MENINGKATKAN KESEJAHTERAAN SANTRI (STUDI KASUS PONDOK PESANTREN DAYAH MINI ACEH) - Juliansyah, Rayhan; Furqani, Hafas; Safitri, Winny Dian (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2026)
This study examines the economic programs implemented in Islamic boarding schools (pesantren) and their contribution to improving the welfare of santri at Dayah Mini Aceh. The research employs a qualitative field approach using a descriptive design, with data collected through in-depth interviews and direct observation. A total of nine informants participated in the study, consisting of the pesantren leader, teachers and program managers, and santri involved in the economic activities.The findings reveal that Dayah Mini Aceh operates four primary business units—drinking water production, goat farming, fish cultivation, and poultry farming—which are managed directly by santri. The compensation system is structured around the concept of pengabdian (devotional service), whereby santri who actively manage these business units receive exemptions from monthly educational fees as a form of non-monetary compensation.The economic programs generate multidimensional benefits for santri welfare. Economically, the fee exemption reduces their financial burden. In terms of food security, santri gain access to consumption from the outputs of pesantren production activities. In addition, the programs contribute to the development of entrepreneurial competencies through direct participation in business management and production processes. Nevertheless, the implementation of these initiatives also faces several challenges, including livestock disease outbreaks, dependence on key managerial actors, and limited financial capital.This study contributes to the literature by documenting a distinctive compensation model in pesantren-based economic empowerment that integrates spiritual values with economic incentives. The findings offer empirical insights into how Islamic boarding schools can promote santri welfare through participatory management of institutional business units.